2020
DOI: 10.3892/ijmm.2020.4463
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroloquinoline quinone attenuates isoproterenol hydrochloride‑induced cardiac hypertrophy in AC16 cells by inhibiting the NF‑κB signaling pathway

Abstract: Pyrroloquinoline quinone (PQQ) is a naturally occurring redox co-factor that functions as an essential nutrient and antioxidant, and has been reported to exert potent anti-inflammatory effects. However, the therapeutic potential of PQQ for isoproterenol hydrochloride (Iso)-induced cardiac hypertrophy has not yet been explored, at least to the best of our knowledge. In the present study, the anti-inflammatory effects of PQQ were investigated in Iso-treated AC16 cells, a myocardial injury cellular model characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Previous studies have reported effects of PQQ on AC16 cells at different concentrations and on other cell types. Wen et al found that PQQ had no effect on AC16 cells at concentrations from 1 to 200 μmol/L [ 10 ]. In our study, although PQQ had no statistically significant effect on cell viability at concentrations from 1 to 10,000 nmol/L, it had adverse effects on AC16 cells at 100,000 nmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported effects of PQQ on AC16 cells at different concentrations and on other cell types. Wen et al found that PQQ had no effect on AC16 cells at concentrations from 1 to 200 μmol/L [ 10 ]. In our study, although PQQ had no statistically significant effect on cell viability at concentrations from 1 to 10,000 nmol/L, it had adverse effects on AC16 cells at 100,000 nmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrroloquinoline quinone (PQQ), a natural bioactive substance, is a water-soluble redox coenzyme that is considered to be a new B vitamin [ 6 ]. PQQ is distributed widely in multiple dietary sources and exhibits potential health benefits, such as anti-inflammatory [ 7 ], anti-oxidative [ 8 ], anti-diabetic [ 9 ], and cardioprotective effects [ 10 ]. Several studies have demonstrated that PQQ deficiency leads to immune dysfunction, growth impairment, and abnormal reproductive performance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging technologies will allow in the future an increasingly precise understanding of the pathophysiology of CVDs and consequent therapeutic advancements. Arrhythmogenic Cardiomyopathy Pathogenic mechanism [8] BMCs Arrhythmogenic Cardiomyopathy Pathogenic mechanism [10] Heart failure - [11] CMs Heart failure Pathogenic mechanism [14] Hypertrophic Cardiomyopathy Drug discovery [16,17] C-MSCs Myocardial ischemia Pathogenic mechanism [24] Arrhythmogenic Cardiomyopathy Pathogenic mechanism/Involvement in disease pathogenesis [25] c-kit + C-MSCs Atrial Fibrillation Pathogenic mechanism [31] FAPs Arrhythmogenic Cardiomyopathy Involvement in disease pathogenesis [35] ECs Hypertension Pathogenic mechanism [39,43] Atherosclerosis Pathogenic mechanism/Involvement in disease pathogenesis [41] Pathogenic mechanism [42] VSMCs Hypertension Involvement in disease pathogenesis [48] Pathogenic mechanism [49] Atherosclerosis Differentiation phenotypes [46] Pathogenic mechanism/Drug discovery [47] AC 16 Hypertrophic Cardiomyopathy Drug discovery [51] Myocardial ischemia Pathogenic mechanism [52] hESC-CMs Hypertrophic Cardiomyopathy Pathogenic mechanism [64,65] hiPSC-CMs Atrial Fibrillation Pathogenic mechanism [76] Hypertrophic Cardiomyopathy Drug discovery [78] Long QT Syndrome Pathogenic mechanism/Drug discovery [79] hiPSC-ECs Hypertension Drug discovery [81] Moyamoya disease Pathogenic mechanism [82] hiPSC-SMCs Supravalvular aortic stenosis syndrome Pathogenic mechanism [83] Bicuspid Aortic Valve-related Thoracic Aortic Aneurysm Pathogenic mechanism/Drug discovery [84] VSMCs and CD14 + cells co-culture Atherosclerosis Pathogenic mechanism [88] [89] ECs and VSMCs co-culture Atherosclerosis Pathogenic mechanism [90]...…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AC 16 cells treated with isoproterenol hydrochloride (Iso) were used as a cardiac hypertrophy model: Iso induced an increase in the size of the cells and the activation of cardiac hypertrophy markers, such as atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP) and β-myosin heavy chain (β-MHC). The aim of the work was to test the anti-inflammatory effects of pyrroloquinoline quinone (PQQ), which resulted to attenuate the activation of nuclear factor k-light-chain-enhancer of activated B cells (NF-κB) phosphorylation, to reduce the Iso-induced accumulation of reactive oxygen species (ROS), to inhibit the expression of hypertrophy markers and to increase the level of matrix metalloproteinase (MMP) in cardiac hypertrophic AC 16 cells [ 51 ]. Another work proposed AC 16 CMs as an ischemia/reperfusion (IR) injury model to evaluate the cytoprotective role of yes-associated protein 1 (YAP1), the main effector of Hippo-signaling pathway.…”
Section: Cardiovascular Cellsmentioning
confidence: 99%